Identification of degranulation inhibitors from rooibos (Aspalathus linearis) tea in rat basophilic leukaemia cells. Issue 10 (19th May 2019) - Morishita, Yuta; Ikeda, Kaoru; Matsuno, Hiroaki; Ito, Hideyuki; Tai, Akihiro
Abstract: Quercetin, luteolin and chrysoeriol were identified from rooibos tea as degranulation inhibitors in rat basophilic leukaemia cells. The degranulation inhibitory activity of chrysoeriol was first discovered in the present study. When quercetin, luteolin and chrysoeriol were mixed in the ratio that occurs in rooibos tea extract, the mixture inhibited antigen- and calcium ionophore-stimulated degranulation to the same degree as that by the whole rooibos tea extract. These findings indicate that these three flavonoids are the key factors underlying the degranulation inhibitory activity of rooibos tea. Abstract :